Feeding Practices in Rearing of Yak and its Bovine Crosses in Ladakh (Indian Journal of Animal Production and Management, 2024)
Yak has been very closely associated with  the culture, religion, and social fabric of the pastoral  people in Ladakh. A study was carried out to  document the feeding practices involved in rearing  of yak and its bovine crosses in Ladakh. Results  indicate that availability of fodder was seasonal with  the fodder being available only between the months  of April to October and had to be stored for harsh  winters. Common property resources (CPRs) were  found to be the primary and only fodder source and  all the yak rearers were feeding a mixed feed  including green, dry and home-grown concentrate  depending on the availability. Usually, the animals  were allowed to graze in the pastures (CPRs) for  most of the time and were stall-fed with collected  and stored grasses only during extremely harsh  winters. During stall-feeding, animals were fed once  a day and it was usually a group feeding of different  animal species all together. Yak rearers in general  lacked the knowledge regarding feed improvement  and feeding of mineral mixture but were aware  about feeding of salt to animals.
Keywords: Ladakh; yak rearers; feeding practices